Studies on the metabolism of meptazinol, a new analgesic drug. - Franklin, R. A. (Blackwell Publishing, 1976)
1 The absorption, metabolism and excretion of the new analgesic meptazinol has been studied in male volunteers following oral and intravenous administration of a mixture of the [1-14C] and [7-3H] labelled compound. 2 After oral dosage, absorption from the gastrointestinal tract was rapid as evidenced by the early attainment of peak plasma radioactivity levels and near complete as shown by only small amounts of radioactivity recovered in the faeces. 3 Although the absorption of the drug was good, the systemic bioavailability was relatively low. Plasma levels of the unchanged drug remained below the limit of detection (20 ng/ml) after an oral dose of 200 mg. However, after intravenous administration of only 20 mg the peak plasma level was approximately 58 ng/ml. Subsequent elimination was rapid and proceeded in an apparently mono exponential manner with a half-life of approximately 2 hours. 4 Excretion of radioactivity was rapid irrespective of the dosage route and took place chiefly via the urine. Over 60% of the administered radioactivity was recovered in the 0-24 h urine collection. Less than 10% of the administered dose was excreted in the faeces. 5 Less than 5% of the drugs was excreted unchanged. The major metabolite appeared to be the glucuronide conjugate of the parent drug. No evidence was found for N-demethylation of the compound. A minor metabolite of the drug which accounted for approximately 7% of the recovered radioactivity has been tentatively identified as 6-ethyl - 6 - (3-hydroxyphenyl) - 1 - methyl-hexahydroazepin - (2H)-2-ONE.